Diaphragm vascular control and the impact of aging - Horn, Andrew Gary (My University, 2024)
Aging is associated with dysfunction of the main inspiratory muscle, the diaphragm, which predisposes the elderly to pulmonary complications and respiratory failure; severely reducing their quality of life. To mitigate the prevalence of these complications, it is crucial to elucidate the mechanistic bases for aging-induced diaphragm dysfunction. Diaphragm contractile function is contingent on the responsiveness of small resistance blood vessels (i.e., arterioles) to facilitate the delivery and distribution of blood flow to match O₂ delivery (Q̇O₂)-to-O₂ demand (V̇O₂). Although structural and functional vasculature alterations have been identified as primary mechanisms for age-related reductions in blood flow capacity, Q̇O₂, and contractile function in locomotory skeletal muscle, the effect of aging on diaphragm blood flow regulation remains unknown. In this sequence of experiments outlined in my dissertation, using a rat model of aging, we quantify diaphragm blood flow during a 1Hz contractile protocol and identify vasomotor pathways associated with age-related vascular dysfunction in diaphragm arterioles. In the studies presented below, we found that aging compromises diaphragm perfusion, vasculature structure, and arteriolar vasoreactivity. In the first study (Ch. 2), we found that aging decreased diaphragm hyperemia and altered regional diaphragm blood flow distribution with 1Hz contractions. A reduced hyperemic response signifies decrements in vascular structure and/or vasodilation and the altered regional diaphragm perfusion indicates potential deficits in vasoconstrictor responsiveness. In the second study (Ch. 3), we found that aging induced arterial rarefaction (i.e., decreased number of feed arteries), impaired endothelium-dependent nitric oxide (NO•)-mediated vasodilation, and blunted myogenic constriction in diaphragm arterioles. NO• is critical to endothelial function and its bioavailability is reduced in the presence of elevated levels of reactive oxygen species (ROS). The myogenic response is modulated by a host of pressure sensitive ion channels, such as potassium (K⁺) channels, which are altered with aging. In the third study (Ch. 4), we confirmed the age-related impairment in NO•-mediated vasodilation and found that aging increased the reliance on ROS-mediated endothelial signaling and decreased myogenic constriction via a voltage-gated K⁺ (KV) channel-dependent mechanism. In toto these studies provide evidence of, and mechanisms for, age-related diaphragm vascular dysfunction and demonstrate that diaphragm vasomotor control is distinctly different from that of other striated muscles.
Keywords: Old age; Inspiratory muscle blood flow; Endothelium; Vascular smooth muscle; Reactive oxygen species; Potassium channels